Proof: Algebra Substitution

Let's prove the following theorem:

if the following are true:
  • aa = (bb) + (cc)
  • a = x
  • b = y

then xx = (yy) + (cc)

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 aa = (bb) + (cc)
2 a = x
3 b = y
Proof Table
# Claim Reason
1 xa = (bb) + (cc) if aa = (bb) + (cc) and a = x, then xa = (bb) + (cc)
2 xx = (bb) + (cc) if a = x and xa = (bb) + (cc), then xx = (bb) + (cc)
3 bb = yb if b = y, then bb = yb
4 yb = yy if b = y, then yb = yy
5 bb = yy if yb = yy and bb = yb, then bb = yy
6 xx = (yy) + (cc) if bb = yy and xx = (bb) + (cc), then xx = (yy) + (cc)

Comments

Please log in to add comments